Load-deformation behaviour of eccentrically loaded SSTT-confined high strength concrete columns - Ma, Chau Khun (Penerbit UTM Press, 2015)
The application of steel-straps confinement or better known as steel-strapping tensioning technique (SSTT) has been proven to be effective in increasing the strength and ductility of High-Strength Concrete (HSC) column comparable to Fiber-Reinforced Polymer (FRP). However, most of the research of confined HSC column has mainly concentrated on concentric loading. In actual practical condition, most of the columns are subjected to eccentric loading. The scarcity of the experimental data for eccentric loaded confined HSC column has prevented the potential use of this type of structure element. In this paper, five HSC columns were tested. The specimens were SSTT-confined and tested with 25mm and 50 mm eccentric loading. The results show that SSTT confinement can increase the strength and deformability of high-strength concrete column, although the strain gradient reduces the confining efficiency. Therefore, smaller capacity enhancement factor should be used in eccentrically loaded SSTT-confined HSC columns compared to concentrically loaded columns. Furthermore, the non-linear theoretical model established in this study can be used for templates for future work on SSTT-confined HSC columns.